Catalytic innovations in fertilizer production from agricultural waste: Enhancing soil health and sustainability - Dawid Skrzypczak; Katarzyna Pstrowska; Anna Niciejewska; Anna Mazur-Nowacka; Łukasz Wilk; Katarzyna Chojnacka (Applied Catalysis O: Open)
Catalytic technologies facilitate the conversion of agricultural waste into high-value fertilizers, enhancing nutrient recovery efficiency while mitigating environmental impacts through reduced greenhouse gas emissions and improved soil management. Selective catalytic reduction (SCR), hydrothermal carbonization (HTC), catalytic pyrolysis, and electrochemical nutrient recovery raise plant-available N, P, and K while reducing life-cycle greenhouse-gas emissions by up to 30 %. These processes support decarbonization efforts and advance circular-economy principles. The article examines catalyst design, process optimization, and the integration of catalytic biomass conversion with renewable-energy systems. Innovative waste-derived fertilizers enhance soil health, lower contamination risks, and strengthen agricultural resilience. Case studies document economic and environmental gains, such as higher nutrient-use efficiency and lower pollutant loads. The review also evaluates regulatory hurdles linked to standardizing and adopting bio-based fertilizers. Future work should explore data-driven catalyst design, microbially assisted nutrient recovery, and the scale-up of promising pilot systems. An integrated catalysis-materials-green-chemistry framework for fertilizer production is presented, advancing food security, improving energy efficiency, and strengthening environmental stewardship.